Three-dimensional (3D) versus two-dimensional (2D) laparoscopic adrenalectomy: A case-control study. (April 2016) - Agrusa, Antonino; di Buono, Giuseppe; Chianetta, Daniela; Sorce, Vincenzo; Citarrella, Roberto; Galia, Massimo; Vernuccio, Laura; Romano, Giorgio; Gulotta, Gaspare
Abstract: Introduction: Laparoscopic adrenalectomy is today considered the gold standard of treatment for adrenal tumors. The development of high definition cameras does not eliminate the major limitation of two-dimensional (2D) laparoscopy: lack of depth perception and loss of spatial orientation. Tree-dimensional (3D) HD laparoscopy was developed as an alternative to conventional 2D laparoscopy. Methods: We report our experience with use of 3D vision system for laparoscopic adrenalectomy. Between January 2009 and March 2015 we performed a total of 52 laparoscopic adrenalectomies. In this case-control study we considered 13 laparoscopic adrenalectomies performed with three-dimensional (3D) vision system as case group. The last 26 procedures made with two-dimensional (2D) HD laparoscopic system represented the control group. We considered primary end-points: operative time, intraoperative complications and conversion rate. We evaluated also quality of depth perception and surgical strain. Results: Although the operative time for the entire surgical procedure was shorter in 3D group, there were no significant differences. The surgeon experienced better depth perception with 3D system and subjectively reported less strain using 3D vision system. Residents and medical students confirmed these data on surgical outcome. Conclusion: 3D system vision does not seem to influence the operative time of laparoscopic adrenalectomy performed by experienced surgeon because the surgical technique request simple tasks. We obtain the better visualization in depth perception with effect on surgical precision. Comparative studies are necessary to verify if 3D can reduce perioperative complication with similar operative time.